2014
DOI: 10.1371/journal.pone.0107138
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Systems for Predicting Mortality after Liver Transplantation

Abstract: BackgroundLiver transplantation can prolong survival in patients with end-stage liver disease. We have proposed that the Sequential Organ Failure Assessment (SOFA) score calculated on post-transplant day 7 has a great discriminative power for predicting 1-year mortality after liver transplantation. The Chronic Liver Failure - Sequential Organ Failure Assessment (CLIF-SOFA) score, a modified SOFA score, is a newly developed scoring system exclusively for patients with end-stage liver disease. This study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
1
14
0
2
Order By: Relevance
“…In contrast we did not demonstrate the presence of pre-operative RRT significantly reduced patient mortality following liver transplantation for ALF. This finding has been replicated previously in observational studies [ 28 ]. Other pre- and post-operative factors are likely to contribute to patient survival, with evidence suggesting response to various therapeutic strategies at day 7 post-transplantation (such as oxygen saturation, hypotension and level of inotropic support) predict survival [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast we did not demonstrate the presence of pre-operative RRT significantly reduced patient mortality following liver transplantation for ALF. This finding has been replicated previously in observational studies [ 28 ]. Other pre- and post-operative factors are likely to contribute to patient survival, with evidence suggesting response to various therapeutic strategies at day 7 post-transplantation (such as oxygen saturation, hypotension and level of inotropic support) predict survival [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…As a result, the presence of RRT may have an additive effect on patient mortality in the presence of other organ support systems but may explain why it does not independently predict patient mortality. However, evidence suggests that the same patient cohort also has a higher rate of acute rejection and hence graft failure [ 28 ]. RRT may therefore provide an important, currently unidentified, individual mechanism in reducing graft failure compared to other organ support systems (as discussed previously) that would explain the effect of RRT in improving graft survival in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severity of liver disease was assessed by CP points and MELD score [ 14 , 15 ]. Severity of illness was also graded by SOFA score according to the six organ systems.…”
Section: Methodsmentioning
confidence: 99%
“…While there is no doubt that the care of critically ill patients with end-stage liver disease (ESLD) has improved with time [5,6], perhaps in part due to better diagnostic and prognostic scoring systems such as the CLIF scores [7,8], this unfortunately does not help answer what additional risks are assumed when transplanting waitlisted candidates from the intensive care unit (ICU). One single-center study by Pan et al has demonstrated that some CLIF scores on admission can predict in-hospital and 1-year mortality post-transplant [9], however larger studies are needed to confirm this finding. Furthermore, while helpful in research, these scoring systems are not widely used in the day-to-day evaluation of inpatient transplant candidates, where the ultimate decision remains center based and primarily driven by anecdotal experience.…”
Section: Reply To ''Is the Post-transplant Survival The Unique Holy Gmentioning
confidence: 99%